Detail Engineering Deisgn Perancangan Detail Engineering Design Infrastruktur Jaringan Komputer RSUD X Kota Y - Aditya Ari Fikri; Diah Ayu Retnani Wulandari; Yudha Alif Auliya (Faculty of Computer Science, University of Jember, 2022)
Detailed Engineering Design Computer networks in hospitals are complete planning drawings that include architectural drawings and detailed elements that support the implementation of computer networks and are supported by technical documents in them. DED is required in hospitals as an attachment to the Network infrastructure submission document used for all hospital operations, health services, and other purposes. The method used in analyzing and designing the Detail Engineering Design is using the Gap Analysis Method (GAP). The proposed recommendations include network topology based on an analysis of existing needs and DED results for the computer network of X City Y Hospital. The topology testing parameters consider QOS (Quality of Service), which consists of ping testing on all devices, Traffic Block Firewall, and web server access. The test results were carried out using three parameters, namely the ping test, traffic block, and web server access, where all tests have been successful and are by the steps in carrying out the test.